Normocalcemic Hyperparathyroidism and Hypoparathyroidism in Two Community-Based Nonreferral Populations - Cusano, Natalie E. (Endocrine Society, 2013)
CONTEXT: Normocalcemic primary hyperparathyroidism is typically identified after referral to a specialty clinic. At diagnosis, patients demonstrate features seen in hypercalcemic primary hyperparathyroidism. Normocalcemic hypoparathyroidism has been discovered after hypocalcemia unmasked after bisphosphonate administration. OBJECTIVE: We hypothesized that screening unselected, nonreferral populations, such as The Osteoporotic Fractures in Men (MrOS) study and Dallas Heart Study (DHS), would identify asymptomatic subjects with normocalcemic hyperparathyroidism and hypoparathyroidism. METHODS: Normocalcemic hyperparathyroidism was defined as serum PTH greater than the upper reference range with normal albumin-adjusted serum calcium, excluding common secondary causes (renal failure [estimated glomerular filtration rate <60 mL/min], 25-hydroxyvitamin D <20 ng/mL, and thiazide use), and normocalcemic hypoparathyroidism as PTH below the reference range with normocalcemia. Cross-sectional data were obtained from MrOS, and longitudinal data (baseline and 8 years) from DHS. RESULTS: In 2364 men from MrOS, we identified 9 with normocalcemic hyperparathyroidism (prevalence 0.4%) and 26 with normocalcemic hypoparathyroidism (1.1%). In 3450 men and women from DHS, we identified 108 with normocalcemic hyperparathyroidism (3.1%) and 68 with normocalcemic hypoparathyroidism (1.9%). Of the 108 normocalcemic hyperparathyroid subjects, 64 had follow-up data. Hypercalcemic primary hyperparathyroidism developed in 1 subject whereas 13 (0.6% of the follow-up cohort) showed persistently elevated PTH levels with normocalcemia. Of the 26 normocalcemic hypoparathyroid subjects with follow-up data, none developed overt hypoparathyroidism and 2 (0.09%) had persistent evidence of normocalcemic hypoparathyroidism. CONCLUSIONS: This study documents normocalcemic primary hyperparathyroidism and hypoparathyroidism identified among community-dwelling individuals. Larger studies are needed to determine the true prevalence and natural history of these parathyroid disorders.